Protein tyrosine phosphatase 11 acts through RhoA/ROCK to regulate eosinophil accumulation in the allergic airway. Issue 11 (30th July 2019) - Xu, Chengyun; Wu, Xiling; Lu, Meiping; Tang, Lanfang; Yao, Hongyi; Wang, Jirong; Ji, Xing; Hussain, Musaddique; Wu, Junsong; Wu, Ximei
Abstract : Src homology domain 2‐containing protein tyrosine phosphatase 2 (SHP2) participates in multiple cell functions including cell shape, movement, and differentiation. Therefore, we investigated the potential role of SHP2 in eosinophil recruitment into lungs in allergic airway inflammation and explored the underlying mechanism. Both SHP2 and Ras homolog family member A (RhoA) kinase were robustly activated in the airway eosinophils of children with allergic asthma and of a mouse model with allergic airway inflammation. Moreover, inhibition of SHP2 activity by its specific inhibitors reverses the dephosphorylation of p190‐A Rho GTPase‐activating protein and in turn attenuates RhoA/Rho‐associated protein kinase (ROCK) signaling, resulting in the attenuation of eosinophil migration in response to platelet‐activating factor stimulation. Specifically, SHP2 deletion in myeloid cells did not affect the number and classification of circulating leukocytes but significantly attenuated the allergen‐induced inflammatory cell, especially eosinophil, infiltration into lungs, and airway hyperreactivity. Notably, genetic interaction between RhoA and SHP2 indicated that RhoA inactivation and SHP2 deletion synergistically attenuated the allergen‐induced eosinophil infiltration into lungs and airway hyperreactivity, whereas overexpression of active RhoA robustly restored the SHP2 deletion‐resultant attenuation of allergen‐induced eosinophil recruitment into lungs and airway hyperreactivity as well. Thus, this study demonstrates that SHP2 via RhoA/ROCK signaling regulates eosinophil recruitment in allergic airway inflammation and possibly in allergic asthma.—Xu, C., Wu, X., Lu, M., Tang, L., Yao, H., Wang, J., Ji, X., Hussain, M., Wu, J., Wu, X. Protein tyrosine phosphatase 11 acts through RhoA/ROCK to regulate eosinophil accumulation in the allergic airway. FASEB J. 33, 11706‐11720 (2019). www.fasebj.org